Modeling of dynamical regimes of two-motor electrical drives with due regard for elasticity and gaps of mechanical transducers - Dochviri, Jumber; Khachapuridze, Oleg (Publishing House of Lviv Polytechnic National University, 2012)
In the paper a mathematical model of two-motor electrical drive with one speed controller and two thyristor converters, by taking into account elasticity's and gaps of mechanical transducers, has been constructed. By using state-space methods, the transfer functions of the object have been determined. Some recommendations for tuning of the regulators have been suggested. Dynamical characteristics that are near to the optimal ones have been obtained by applying MATLAB. Стаття присвячена побудові математичної моделі двомоторного електроприводу з одним регулятором швидкості і двома тиристорними перетворювачами (конвертерами) з урахуванням пружності і люфтів механічних перетворювачів. З використанням методів простору станів сформульовано передавальні функції об’єкту. Запропоновано рекомендації для налаштування регуляторів. За допомогою програми MATLAB отримано динамічні характеристики, що є близькими до оптимальних.
Моделювання динамічних режимів двомоторних електроприводів з урахуванням пружності та люфтів механічних перетворювачів
Keywords: dynamics; two-motor electrical drive; modeling